Examining the Effects of Juvenile Drug Treatment Courts: A Systematic Review and Meta-Analysis - Tanner-Smith, Emily E. (Criminal justice and behavior, 2024)
We meta-analytically examined program graduation rates among juvenile drug treatment court (JDTC) participants, the effects of JDTCs on recidivism and substance use outcomes, and the variability in these effects. We systematically searched for controlled evaluations examining the effects of U.S.-based JDTCs relative to traditional juvenile adjudication and used mixed-effects meta-regressions with robust variance estimates. We identified 55 eligible samples (providing data from 12,310 participants); the overall certainty of evidence was low or very low. The average graduation rate among JDTC participants was 54.74% (95% confidence interval [CI] [0.50, 0.59]). JDTCs had modest beneficial effects on general recidivism assessed during court supervision (odds ratio [OR] = 1.38, 95% CI [1.03, 1.84]) but these effects did not persist after program completion. Correlational analyses suggest JDTCs may be effective when program enrollment and service provision are better tailored to youth’s treatment needs. However, due partly to implementation failures, JDTCs may have minimal to no effects on postprogram recidivism.